Organização da atenção básica à saúde de Jequié-BA: uma agenda a ser concluída - Menezes, Marcus Vinícius da Silva (2006)
Study that considers the strategy of organization of the basic attention to health accepted in the city of Jequié-BA, in the period of 1998 -2006, taking the offer of services, the capacity installed, the politics of human rescourses and the fluent of treatment like axis of analysi. It has for specific objectives: to characterife the public net of establishments of basic attention to the healt, to describe the production of the services offered for the basic attention to the health (medical appointments for basic specialty, appointments of nursering, medical, nursering and odontologyc procedures), indicate the politic of Human Recourses to SUS in the basic net of local health and to argue the fluent of treatment of the net of attention to the health of the city reported. It is about a documentary study that it used quantitatives datas, through informations tabulated in the DATASUS and qualitative datas, as the analysis of document that treat of organization of services of the SMS of Jequié-BA. The study show that although of the municipalizarion process having allowed the amplification of the basic net of services of the city reported, still persist obstacles for the expansion of the strategy of health of family as while politics of reorganization of the basic attention. There is a predominance af health stablishments that offer services of selective primary attention, that represented in 2005 aproximately 40% of the total of existing units in the met. The offer of medical appountments in the city of Jequié (BA) had a considerable retraction in contrast of the nursering appointments that had a significant increment enter 1998 to 2005, bung that this sitrations suggestes a restrained demand for the medical appointments in this period. The improvement of the relations of working bond among the health professionals, was not gone deep for the institution of a Plan of Functions Career and Salaries (PCCS), pointing a little attractive scene to the development in the career for these professionals. The qualification for the work had greater intensity in yers 2000, 2001 and 2002, corresponding the implementation of the complete administration of the municipal system, while that the years subsequent were marked for the reduction of the activities of formation of the human recourses in spit of the crescent lawsuits for knowledges relativeto the implantion of programs and practical attendance in the city ambit. The organization of the attendance flow was marked by two moments that pointed unitially a net broken up with a flow of attendance in a only direction and in second moment visualized an approad of the system with the integrated net, presenting a dynamics of reference and against-reference. This scene, however, was not enough to modify the picture of segmentation of the health system, even so if presents as effort of the municipal administration in direction the constituiion of a regulatoric complex, defined as whole of health establishments that articulate in complementary charater in the offer of attention to the therapeutical project of the users.